2020
DOI: 10.1177/0961000620967736
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress measures of tenure-track librarians

Abstract: This study sought to measure occupational stress levels of tenure eligible academic librarians quantitatively and explores the connections between occupational stress and institutional supports. Researchers administered the Job Stress Survey™ to 109 academic librarians in tenure eligible positions. These data were then analyzed and correlated with participants’ responses in an earlier study which measured tenure confidence and access to institutional supports. Findings showed that lack of support contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Cameron et al looked specifically at the occupational stress level of tenuretrack librarians and found an above average rate of job stress severity among respondents, primarily stemming from a lack of institutional support. 10 Davis Kendrick found that tenure and promotion as a system, both being present or not in libraries, served as an enabler for low morale by creating problematic hierarchy, as well as encouraging librarians to keep tenured positions despite being unhappy in the job. 11 Shupe et al found that librarians who experienced high role overload also experienced higher levels of stress, burnout, and job dissatisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cameron et al looked specifically at the occupational stress level of tenuretrack librarians and found an above average rate of job stress severity among respondents, primarily stemming from a lack of institutional support. 10 Davis Kendrick found that tenure and promotion as a system, both being present or not in libraries, served as an enabler for low morale by creating problematic hierarchy, as well as encouraging librarians to keep tenured positions despite being unhappy in the job. 11 Shupe et al found that librarians who experienced high role overload also experienced higher levels of stress, burnout, and job dissatisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…13 In a recent study of occupational stress and tenure-track librarians, Cameron, Pierce, and Conroy found that factors related to research support produced the most stress, but these stressors could be alleviated by research training and mentoring. 14 Other researchers confirm that the need for research training and institutional support is especially acute for early-career librarians on the tenure track, including librarians of color. 15 However, Hollister and a peer support network for feedback on their writing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stress from caretaking responsibilities for workers who lost childcare or other forms of support during the pandemic has exacerbated issues of esprit de corps and well-being in the workplace. For academic librarians, who are pre-tenure or otherwise expected to contribute publications and presentations to library scholarship (and already at a high-stress time in their careers), 23 the pandemic has created additional challenges to those with caretaking responsibilities, particularly women. 24,25 These workers already experience burnout at higher rates.…”
Section: Library Staffing Challengesmentioning
confidence: 99%